Growth and Redistribution: Is there 'Trickle Down' Effect in the Philippines? - Danileen Kristel C. Parel (Philippine Institute for Development Studies (PIDS), 2014)
This paper aims to explore the determinants of household income and expenditure growth, and assess whether the poor are benefiting from economic development. Using regression analysis, five factors were examined: (1) location of the household, (2) access to infrastructure, (3) changes in rice prices, (4) peace situation, and (5) initial household endowments. The most important finding is that impacts of the five factors vary significantly across households belonging to different income groups - the rich benefit more than the poor. This calls for an effective policy intervention in targeting the poor.
Keywords: 330; poverty; education; inequality; Philippines; growth; redistribution